[0] [1] [2] [3] [4] [5] [6] [7] [8] [9] [10] [11] [12] [ 13 ] [14] [15] [16] [17] [18] [19] [20] [21] [22] [23] [24] [25] [26] [27] [28] [29] [30] [31] [32] [33] [34] [35] [36] [37] [38] [39] [40] [41] [42] [43] [44] [45] [46] [47] [48] [49] [50] [51] [52] [53] [54] [55] [56] [57] [58] [59] [60] [61] [62] [63] [64] [65] [66] [67] [68] [69] [70] [71] [72] [73] [74] [75] [76] [77] [78] [79] [80] [81] [82] [83] [84] [85] [86] [87] [88] [89] [90] [91] [92]

z- (z)

(s2 + a2)(s2 + bn

(s + a)*

(s2 + c)2

s(s + a)(s + 6) X X(s + c)(s + d)

s(s + a)Ms + b)=

1--1

- 4 (1 cos ) (1 - cos bli) bi = - 2 (cos ah + cos 6h); = 2 + 4 cos a/i cos bft;

KoiZa); 1 = -4; 2 = 6»; = -4; 64 = *; = 6-""

1 + ,-1 + bz-+bz-+bz-i

0 = 4 (1 - cosc/i)"

bi = - 4 cos ; bg = 2 + 4 cos" ah;

bs = bi; bi=\

(1 + biz-i + bz- + bgz-s + b42-«).

abed ,

Ko = cth(i )(l B)x *

X(l-C)(l-£>) 1 = -( + + + 0); 6a = + + +++; 63 = - ( + £> + +); biABCD; = -; = -*;

(1 - *i2-i - -- - 6-3 + -*},

Ko = a.h(l-A)Hl-Bf

6i = - 2 ( + ); 6= 2+ 2+4;

6 = -2(+); 64 = =2;



13 is)

- (Z)

>i.(s + c){s-\-d) 4 --

a£rf

+ S){1-C)(1-D) = (2 VB cos Ah + + D); . ba = + CZ) + 2 (C + D) }˸ cos ,-63 = - ( + D) - 2C£> /B cos ;

64 = BCD; = D = fi-*; =

= e""; = > - bV4

-.-eft.

s(s2+te + a) X X (s2 + ds + c)

(1 + + V + - + -*).

"" (1-2/8 +

+ ) (1 - 2 /D cos +D) fcj = 2 (JB cos + D cos ); bj = + D + 4 lBD cos cos ; = . 2(8 + + /8); t4 = BD; =~**; D=e-\ K = Va-blA;

s(s + b5 + c)

«o = ,,(, 7 ,4 s +6)?

fci=~4 JBcosWi; 5=2--4 cosaA =-4 FB cos ; 64=5". Be-\ = Va - b/A

s(s+a){s-\-c)(s+d)

(1 + hz- + b,3-a + -«+ b42-«).

Kt

2(1 - 8)(1 - ) X X (1 - D) bj = - (2cos + + D); bj = I + CD + 2 ( + D) cos oft; bg = - (C + D) - 2CD cos aft; *4 = CD; C-=e-\ D = e



n/ii

- (z)

(I + 6i2-i+ V"* + V+

" - 4;j , (i- cosbh)

bj = - 2 (cos ah + cos bh);

bj = 2 + 4 cos oh cos bh; 63 = 61; 64=1

5(s + o)

(1 + 6ig-i+ - + bz-+ ba = "; 63.= - 43; b = ;

s (s2 + aY

(1 + 6iz~i + 622-2+ 632-8+ 642-*),

/<o = 4aft(i coso/i)2 =

6, = - 4 cos ah; 6 = 2 + 4 cos* ali;

63 = 61; 64= 1

(s + a)(s + 6)(s+c)x X(s+d)(s + g)

1 + bj2-i + 6.2-2+ 632-3+ 6,2-4+

Kq =

1-2-1

abcdg

a(\-A)(\-B){\-C)X X(l-D)(l-G)

61 = -(+ + + + 0);

62 = ++£>++1) + + DC + {A + B+C + D)G;

63 = - ( + + +

+ BDC) - ( + + /7+ + + BD + £?C)<?;

64 = ABCD + ( + ABD + + + BDC) ;

6 = -0; = -**: 6 = "";



[0] [1] [2] [3] [4] [5] [6] [7] [8] [9] [10] [11] [12] [ 13 ] [14] [15] [16] [17] [18] [19] [20] [21] [22] [23] [24] [25] [26] [27] [28] [29] [30] [31] [32] [33] [34] [35] [36] [37] [38] [39] [40] [41] [42] [43] [44] [45] [46] [47] [48] [49] [50] [51] [52] [53] [54] [55] [56] [57] [58] [59] [60] [61] [62] [63] [64] [65] [66] [67] [68] [69] [70] [71] [72] [73] [74] [75] [76] [77] [78] [79] [80] [81] [82] [83] [84] [85] [86] [87] [88] [89] [90] [91] [92]

0.0038